In the Shadow of War : Stories of Resilience and Change Among Ukrainian Women Entrepreneurs - Mysko, Kateryna; Kania, Karolina Anna; Ali, Tanweer; Vysoká škola ekonomická v Praze. Podnikohospodářská fakulta (2025)
This Bachelor’s Thesis investigates how Ukrainian women entrepreneurs have adapted to the conditions of Russia’s full-scale invasion. The aim is to identify the main challenges they faced, the strategies they used to sustain their businesses, and the values they sought to preserve. The research is based on seven semi-structured interviews with entrepreneurs from Kyiv, analysed through thematic analysis. Findings reveal that while women confronted severe obstacles such as client loss, displacement, financial insecurity, and stress, most demonstrated resilience through entering new markets, diversification of services and products, and logistical adjustments, while one business was forced to close. The study illustrates the resilience of women-led businesses under extreme uncertainty and contributes to the broader understanding of entrepreneurship in crisis contexts.
Vedoucí práce: Karolina Anna Kania
Bakalářská práce (Bc.)—Vysoká škola ekonomická v Praze. Fakulta podnikohospodářská, 2025
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2025
Způsob přístupu: Internet
Keywords: bachelor of business administration [obor bakal. práce]; bakalářské práce; bachelor's theses